The use of youtube in Arabic speaking skills during open and distance learning (ODL) - Ijlal Saja @ Mearaj,; Syaza Marina Ramli,; Anuar Sopian,; Abdul Qayyum Abdul Razak, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Youtube is one of the platforms to convey knowledge through learning and teaching Arabic. Furthermore, the sharp increase in the use of Youtube occur when COVID-19 pandemic hit the country. This also affects education that causes it to be done through open and distance learning (ODL). However so, not all students are able to conduct ODL for Arabic language course smoothly. Moreover, Arabic speaking skills was rated at the lowest level among students who considers the Arabic language is difficult to master. Therefore, this study was conducted to identify the level of challenges faced by students in learning Arabic during ODL. In addition, it aims to produce Arabic speaking skills learning videos via Youtube during ODL. Finally, an analysis for the student’s tamthiliy videos was conducted to improve Arabic speaking skill during ODL. This study is a survey-based research by using questionnaires and documents. The questionnaire instrument was used to identify the challenges and Youtube usage level among 300 students selected by random sampling from UiTM Melaka Branch. Whereas the documents were used to develop instructional video and analyse tamthiliy video. The collected data was then analysed descriptively and presented in the form of tables and diagrams. The findings that there were challenges faced by students in learning the Arabic language through ODL during the COVID-19 pandemic. Nevertheless, the development of learning videos and tamthiliy helps students to master Arabic speaking skill well in ODL learning. This study suggests future research to investigate the challenges aspects faced by Arabic language lecturers during COVID-19 pandemic and develop interactive teaching materials that is suitable for current situation.